Impasses in Justice - Arthur T. Vanderbilt (Washington University Law Quarterly, 1956)
It is not oversimplifying our problem too much to say that at the bottom of all our difficulties in court reform lie: (1) the equalitarian and antiprofessional movement of the Jacksonian Era in the second quarter of the nineteenth century, and (2) (this I fear will shock many) the failure of our law schools generally to recognize as their most important responsibility to society the improvement of the administration of justice.
Keywords: Administration of justice